Caracterização trófica da ictiofauna da Represa do Beija-Flor, na Estação Ecológica de Jataí, Luiz Antônio, SP - Oliveira, Elisa Martins de (Universidade Federal de São Carlos, 2011)
The feeding habits, reproduction and growth of omnivores, herbivores, detritivores and iliófagos fish species from the Beija-flor reservoir in Jataí Ecological Station were investigated. This provides information on the trophic interaction between species, feeding habits, establishing guilds and also provides subsidies for monitoring the the Beija-flor reservoir. Emphasis was placed on Prochilodus lineatus, presented as a larger sample in this study, so the reproduction and growth of only this species was analyzed. Eleven samplings were made between September 2008 and October 2009. The diet was assessed through the food importance index. Three species showed an herbivorous diet (Leporinus striatus, Schizodon nasutus and Metynnis sp.), two species were omnivorous with a tendency to insectivory (Astyanax altiparanae and Astyanax fasciatus), two species were omnivorous with tendency to herbivory (Leporinus aff. friderici and Geophagus brasiliensis), one species was ilyophagous (Cyphocarax modestus) and one species was detritivore (Prochilodus lineatus). The reproduction of Prochilodus lineatus occurred between November and February and their allometric growth was negative. The richness of organic matter in the sediment of the Beija-flor reservoir is evidenced in the high proportion of organic matter found in the C. modestus and P. lineatus stomach contents. Detritus was a food source of higher quality for these species so this reservoir provides an important place of feeding. There is no seasonal pattern of feeding overlap between species, that was caused by significant amounts of feeding overlap occurred in the both seasons. The analysis of dietary overlaps showed that food partitioning was higher within detritivores. Although there was overlap between many the species, there is no competition between them because the niche was shared. The Beija-flor reservoir is an environment where the detritivore food chain has an important role in the system because the reservoir is an ecosystem of decomposition.
Keywords: Peixe - alimentação; Mogi-Guaçu, Rio, Bacia (SP e MG); Estação Ecológica de Jataí; Sobreposição alimentar; Ecologia trófica de peixes; CIENCIAS BIOLOGICAS::ECOLOGIA